2020
DOI: 10.1177/1120672120969045
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic adverse effects of taxanes: The Mayo Clinic experience

Abstract: Purpose: To investigate ophthalmic side effects of taxanes and compare side effect frequency, requirement for cessation of taxane therapy, visual acuity outcome, and concurrent systemic effects between paclitaxel and docetaxel. Methods: Patients taking taxanes at a single center from 1/1/2010 to 2/29/2020 were retrospectively reviewed for clinical characteristics, treatments, and concurrent systemic adverse effects. Results: Of 1918 patients, 22 (1.1%) experienced an ophthalmic side effect that came to the att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…However, we reveal important data linking safety signals for lens disorders with venetoclax use. Combination therapy with BRAF/MEK inhibitors such as encorafenib/bimetinib and dabrafenib/ reported that taxanes such as paclitaxel, nab-paclitaxel, and docetaxel induce macular edema at a low frequency(42,43).Our results suggest that nab-paclitaxel and paclitaxel may increase the risk of retinal damage. In our study, blinatumomabTanaka et al: Ocular Adverse Reactions Associated With Anticancer Drugs 4445…”
mentioning
confidence: 57%
“…However, we reveal important data linking safety signals for lens disorders with venetoclax use. Combination therapy with BRAF/MEK inhibitors such as encorafenib/bimetinib and dabrafenib/ reported that taxanes such as paclitaxel, nab-paclitaxel, and docetaxel induce macular edema at a low frequency(42,43).Our results suggest that nab-paclitaxel and paclitaxel may increase the risk of retinal damage. In our study, blinatumomabTanaka et al: Ocular Adverse Reactions Associated With Anticancer Drugs 4445…”
mentioning
confidence: 57%
“…Paclitaxel-based chemotherapy is known to cause ocular side effects including meibomian gland dysfunction [ 4 ], canalicular obstruction [ 4 ], diplopia [ 4 ], keratitis [ 9 ], CME [ 10 ], scintillating scotoma [ 11 ], and possibly glaucoma [ 12 , 13 ]. Das et al .…”
Section: Discussionmentioning
confidence: 99%
“…Non-ocular taxane-associated adverse effects include, but are not limited to, hypersensitivity reactions, myelosuppression and immunocompromise, neurotoxicity, cardiac toxicity, and myalgia [ 3 ]. Ocular side effects are seen in 1.1% of patients receiving taxanes [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…T-CME is a rare side effect of taxanes, with an incidence of about 0.2–0.5% ( 3 , 4 ). The first case of T-CME was reported in 2003, caused by docetaxel ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Albumin-bound paclitaxel (nab-paclitaxel, Abraxane) is an albumin-stabilized paclitaxel nanoparticle formulation with potent antitumor effects than paclitaxel in metastatic breast cancer that has failed combination chemotherapy or recurred within 6 months of adjuvant chemotherapy ( 2 ). Cystoid macular edema (CME) is a rare complication caused by nab-paclitaxel ( 3 , 4 ). Here we report the first case of nab-paclitaxel-induced CME treated with intravitreal ranibizumab (IVR) and review the literature about nab-paclitaxel-related CME.…”
Section: Introductionmentioning
confidence: 99%